GUEST PERCEPTIONS OF NUTRITIONAL INFORMATION ON HOTEL MENUS: A SURVEY-BASED STUDY (International Journal of Food and Nutritional Sciences, 2021)
This study investigates guest perceptions of nutritional information on hotel menus through a comprehensive survey-based approach. In an era where health consciousness is growing, understanding how nutritional labeling influences consumer choices is crucial for the hospitality industry. The survey, distributed among a diverse demographic of hotel guests, assessed their awareness, preferences, and the impact of nutritional information on their dining decisions. The findings reveal that a significant portion of guests considers nutritional information a critical factor in menu selection, with preferences varying across age groups, dietary needs, and health goals. Guests who frequently prioritize healthy eating habits showed a strong preference for menus that include detailed nutritional content, such as calorie counts, macronutrient breakdowns, and allergen warnings. The study also highlights a notable difference in perceptions based on the type of nutritional information provided, with simple calorie counts being less influential than more comprehensive data. Additionally, guests expressed a higher likelihood of choosing healthier options when nutritional information was prominently displayed. The research underscores the potential for hotels to enhance customer satisfaction and loyalty by incorporating clear and detailed nutritional labeling on menus. These findings suggest that hotels can benefit from tailoring their menu offerings and presentation to align with the evolving health-conscious trends among consumers, ultimately fostering a positive dining experience. The study concludes that integrating nutritional information on menus is not only a response to guest demand but also a strategic move to attract and retain health-conscious customers in a competitive hospitality market.